Relación entre la satisfacción laboral y la intención de rotación en el sector automotriz - Rodríguez Santos, Carlos Javier; VARGAS SALGADO, MARIA MARISELA (2020)
http://natal.uern.br/periodicos/index.php/RTEP/index